Protocol for a randomised pilot multiple centre trial of conservative versus liberal oxygenation targets in critically ill children (Oxy-PICU). Issue 12 (14th December 2017) - Jones, Gareth A L; Ramnarayan, Padmanabhan; Raman, Sainath; Inwald, David; Grocott, Michael P W; Eaton, Simon; Ray, Samiran; Griksaitis, Michael J; Pappachan, John; Wiley, Daisy; Mouncey, Paul R; Wulff, Jerome; et al.
Abstract : Introduction: Optimal targets for systemic oxygenation in paediatric critical illness are unknown. Observational data indicate that high levels of arterial oxygenation are associated with poor outcomes in resuscitation of the newborn and in adult critical illness. Within paediatric intensive care units (PICUs), staff prevent severe hypoxia wherever possible, but beyond this there is no consensus. Practice varies widely with age, diagnosis, treating doctor and local or national guidelines followed, though peripheral blood oxygen saturations (SpO2 ) of >95% are often targeted. The overall aim of this pilot study is to determine the feasibility of performing a randomised trial in critically ill children comparing current practice of liberal SpO2 targets with a more conservative target. Methods and analysis: Oxy-PICU is a pragmatic, open, pilot randomised controlled trial in infants and children requiring mechanical ventilation and receiving supplemental oxygen for abnormal gas exchange accepted for emergency admission to one of three participating UK PICUs. The study groups will be either a conservative SpO2 target of 88%–92% (inclusive) or a liberal SpO2 target of >94%. Infants and children who fulfil all inclusion criteria and none of the exclusion criteria will be randomised 1:1 by a secure web-based system to one of the two groups. Baseline demographics and clinical status will be recorded as well as daily measures of oxygenation and organ support. Discharge outcomes will also be recorded. In addition to observational data, blood and urine samples will be taken to identify biochemical markers of oxidative stress. Outcomes are targeted at assessing study feasibility with a primary outcome of adequate study recruitment (target: 120 participants). Ethics and dissemination: The trial received Health Research Authority approval on 1 June 2017 (16/SC/0617). Study findings will be disseminated in national and international conferences and peer-reviewed journals. Trial registration number: NCT03040570.